2018
DOI: 10.1016/j.bjpt.2017.12.005
|View full text |Cite
|
Sign up to set email alerts
|

Transcutaneous electrical nerve stimulation and interferential current demonstrate similar effects in relieving acute and chronic pain: a systematic review with meta-analysis

Abstract: Transcutaneous electrical nerve stimulation and interferential current have similar effects on pain outcome The low number of studies included in this meta-analysis indicates that new clinical trials are needed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
44
0
3

Year Published

2019
2019
2023
2023

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 57 publications
(49 citation statements)
references
References 43 publications
0
44
0
3
Order By: Relevance
“…Regarding the use of ICT and its long-term effects, four systematic reviews with meta-analyses have been published to date. Two of these [14,38] addressed the use of ICT in the general management of acute and chronic skeletal muscle pain, including the management of knee OA. The others addressed the use of electrical stimulation, including ICT, specifically in relation to the management of knee OA [39,40].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Regarding the use of ICT and its long-term effects, four systematic reviews with meta-analyses have been published to date. Two of these [14,38] addressed the use of ICT in the general management of acute and chronic skeletal muscle pain, including the management of knee OA. The others addressed the use of electrical stimulation, including ICT, specifically in relation to the management of knee OA [39,40].…”
Section: Discussionmentioning
confidence: 99%
“…Fuentes et al (2010) [38] stated that the inclusion of ICT in a multimodal treatment program promotes pain relief in chronic musculoskeletal conditions. Almeida et al (2018) [14] reported the effectiveness of ICT for improving pain and function analysed using the WOMAC. [39] highlighted ICT as a promising treatment for relief of pain associated with knee OA.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The typical frequency range is 2-150 Hz for TENS and 1 K-10 K Hz for IFT. Positive results in pain relief have been achieved by both of them [5].…”
Section: Introductionmentioning
confidence: 94%
“…It penetrates deeper into the skin than lowfrequency equipment, such as TENS, with less discomfort [7][8]. However, its clinical impact is still controversial in low back pain, with few studies substantiating its efficacy, especially in relation to acute pain [10][11]. Thus, the objective of the present study was to evaluate its effect on young women with acute low back pain.…”
Section: Introductionmentioning
confidence: 99%